Rapid expansion of Ulva blooms in the Yellow Sea, China through sexual reproduction and vegetative growth. (May 2018) - Cui, Jianjun; Shi, Jinting; Zhang, Jianheng; Wang, Lintao; Fan, Shaoying; Xu, Zhenyang; Huo, Yuanzi; Zhou, Qiaoyun; Lu, Yuwei; He, Peimin
Abstract: Green algal blooms have occurred in the Yellow Sea for 11 consecutive years since 2007. A "seed bank" comprising micro-propagules including gametes, meiospores, and zygotes, played an important role in the rapid formation of a green tide. In the present study, germination differences among zygotes, meiospores, and gametes were examined. The growth ability and maturation period of alternating generations of sexual Ulva prolifera strains were also assessed. The zygote and meiospore germination rate was 91.67% and 80.29%, respectively, approximately three times greater than that of gametes (30%). In addition, the highest daily growth rate of sporophytes and gametophytes was 266.7% and 288.1%, respectively, and the maturation period of sporophytes and gametophytes was 35.7 and 31.3 days, respectively. These results indicate that sexual reproduction and vegetative growth are mainly responsible for the rapid expansion of macroalgal blooms in the Yellow Sea. Highlights: The floating Ulva for the Yellow Sea blooms presents sexual reproductive pattern. The maturation period of the floating Ulva could maintain over one month. Rapid vegetative growth was the reason for huge Ulva biomass in the Yellow Sea.